A critical review on radioactive waste management through biological techniques - Natarajan, Varagunapandiyan; Karunanidhi, Mahalakshmi; Raja, Balamanikandan (Environmental science and pollution research international, 2020)
Our world is subject to various kinds of pollution and contamination due to rapid growth and development of industrialization. Though, industries are helping to improve the human life style in many ways in day to day life such as power generation to treatment of diseases. At the same time, industries emit the waste which causes major environmental pollution and leads to harmful for all living organism. As the renewable energy sources are depleting, energy/power generation become a major research around the world. Nuclear energy is one of the promising energy to sort out the energy demand, but the problem associated with the nuclear energy is the management and treatment of radioactive waste/emission/effluent since which is more dangerous to all living organism. There is a large scale contamination of radioactive waste associated for the past 60 years of global nuclear activity. It is necessary to pay special attention to the management of radioactive wastes in order to approach pollution-free environment and avoid diseases to living organism through various clean-up strategies. In this review, we discussed the wide ranges of strategies available for radioactive waste management such as physical, chemical, and biological methods. Bioremediation may be the powerful tool for treatment of radioactive wastes. Additionally, discussed on recent advancement have been made in treatment of radioactive waste through microbial transformation as well as phytoremediation which play a major role in disposal of radioactive waste.